Novel design and microelectronic analysis of highly stable Au/Indigo/n-Si photodiode for optoelectronic applications - Manthrammel, M. Aslam; Yahia, I. S.; Shkir, Mohd; AlFaify, S.; Zahran, H. Y.; Ganesh, V; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2019)
In the current work, the authors studied a hybrid organic-inorganic photodiode combining n-type mono-crystalline silicon (n-Si) and indigo dye where the natural dye indigo has been applied as an interfacial layer between Gold (Au) and n-Si. The electrical and photo-response characteristics of photodiode based on indigo dye were investigated through current, conductance and capacitance studies measured under the wide illumination intensity and frequency ranges. The frequency dependency of capacitance-voltage (C-V) and conductance-voltage (G-V) characteristic properties of the Au/Indigo/n-Si photodiode was examined in the frequencies varying from 100 kHz to 1 MHz in view of the effects of series resistance (R-s), the concentration of donor atoms (N-d) and density of interface states (Nss). The C-V and G -V studies indicate that the N-ss and R-s are key factors which are strongly influencing the electrical properties of the fabricated Photodiode. From the obtained results, the fabricated Au/Indigo/n-Si photodiode can be a promising contender for electro-optic device engineering.
Keywords: Highly stable indigo dye; Organic photodiode; Current-voltage analysis; Capacitance-voltage; Series resistance and density of states